Hubungan Pengawasan Orangtua Dan Pergaulan Teman Sebaya Dengan Karakter Kristiani Siswa SMP Negeri 3 Sipoholon Tahun Pembelajaran 2023/2024 - Murniwati Telaumbanua; Binur Panjaitan; Betty A.S Pakpahan (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The research objectives were to determine: 1) the relationship between parental supervision and the Christian character of student at SMP Negeri 3 Sipoholon, 2) the relationship between peer interaction and the christian character of student at SMP Negeri 3 Sipoholon, 3) the relationship between parental supervision and peer interaction with christian character, Sipoholon 3 public Midlle School Student. In this research, a quantitative descriptive inferential approach was used. The population ofof all student at SMP Negeri 3 Sipoholon for the 2023-2024 academic year is 262 people.